An Analysis of ESL Negation by Indonesian Learners of English - Ikhsan Ikhsan (International Journal in Applied Linguistics of Parahikma, 2021)
It is widely assumed that constructing negation in an L2 is often quite affected by the syntactic features of the speakers’ mother tongue. This study, therefore, set out to assess the English negation construction, particularly in the context of Indonesian learners of English in Sulawesi-Barat. Data for this study were collected using an interview to investigate the pattern of negation construction and the L1 influences related to the construction. For the purpose of analysis, the data transcription was carried out on the completion of the interview and segmented into AS-Unit. Results suggest that the participants mostly constructed negation in the form of auxiliary + not + phrase in their second language. The second major finding was that there are transfers from the students’ L1 in constructing negation in their L2. The example of English negation which might be not representative enough makes an overall conclusion about English negation construction extremely difficult.